2005
DOI: 10.1159/000088144
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Effects of Carbohydrates and Aromatic Amino Acids on <i>Clostridium botulinum </i>Toxin Gene Expression Using a Rapid Competitive RT/PCR Assay

Abstract: A rapid competitive RT/PCR assay was developed to determine the effects of nutrients on Clostridium botulinum type E toxin gene expression. The type E strain (EVH) was grown in a nutrient-rich broth containing 1% glucose (base medium). Toxin gene expression was quantified at both mid and late exponential phases of growth. It was found that toxin encoding mRNA levels were highly growth phase dependent with elevated levels found in late exponential phase compared to mid exponential phase. Changing the carbohydra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…The expression pattern of plc could potentially reflect an evolutionary strategy to increase substrate availability in crowded environments by increasing toxin (phospholipase) production. A similar up-shift in transcription of the gene encoding botulinum neurotoxin (cntA) has been observed in Clostridium botulinum (Sharkey et al, 2005;Shin et al, 2006). A difference in transcript levels between strains T9 and S3 by up to a factor 10 was shown in Fig.…”
Section: Transcript Levels Of Plc and Production Of A-toxinsupporting
confidence: 53%
“…The expression pattern of plc could potentially reflect an evolutionary strategy to increase substrate availability in crowded environments by increasing toxin (phospholipase) production. A similar up-shift in transcription of the gene encoding botulinum neurotoxin (cntA) has been observed in Clostridium botulinum (Sharkey et al, 2005;Shin et al, 2006). A difference in transcript levels between strains T9 and S3 by up to a factor 10 was shown in Fig.…”
Section: Transcript Levels Of Plc and Production Of A-toxinsupporting
confidence: 53%
“…Understanding the activity of bacterial virulence genes at low temperatures is a key to establishing novel strategies to ensure the safety of refrigerated foods. To date, all published studies on type E neurotoxin gene expression have been conducted at 30°C or higher (3,18,22,23). However, to the best of our knowledge, no report is available on the type E neurotoxin gene expression at low temperatures or on the relative expression of the six type E neurotoxin cluster genes.…”
mentioning
confidence: 99%
“…It is possible that this is a growth rate phenomenon, where toxin production is enhanced due to a lowered growth rate, as reported for Clostridium difficile under stress conditions (30). Sharkey et al (39), however, indicated that for nonproteolytic C. botulinum type E, an increased growth rate was associated with an increased expression of cntE, while the presence of sorbic acid and sodium nitrite reduced both the growth rate and expression of cntE (40). Lövenklev et al (27,28) also reported an inhibitory effect of nitrite on cntB expression.…”
Section: Discussionmentioning
confidence: 95%
“…However, little is known about the direct regulation of the neurotoxin gene (cnt) or of neurotoxin formation by nonproteolytic C. botulinum type E. While a positive regulator, cntR, has been found in other types of C. botulinum, it appears to be absent in C. botulinum type E (9,24,36). Several in vitro methods have been developed for monitoring cnt expression in proteolytic C. botulinum and nonproteolytic C. botulinum, including a gene reporter system (12), competitive reverse transcription (RT)-PCR (29,39,40), and quantitative RT-PCR (qRT-PCR) (10,23,27,28,42). Experiments using these methods found a peak in neurotoxin gene expression in late exponential or early stationary phase.…”
mentioning
confidence: 99%